2012
DOI: 10.1179/2042618612y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Intra-rater reliability of an experienced physiotherapist in locating myofascial trigger points in upper trapezius muscle

Abstract: Objectives: Myofascial trigger points (MTrPs) are considered the principal clinical feature of myofascial pain syndrome (MPS). An MTrP consists of spot tenderness within a taut band of muscle fibers and its stimulation can produce both local and referred pain. The clinical diagnosis of MPS depends on correct history taking and a physical examination aimed at identifying the presence of MTrP. The purpose of this study was to investigate the intra-rater reliability of a palpation protocol used for locating an MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 31 publications
(33 reference statements)
1
28
0
6
Order By: Relevance
“…Additionally, study participants with pain had symptoms suggesting endometriosis which limited the number with pain without an endometriosis history. We did not assess sensitization in locations remote from the pelvis nor did we identify a second physiatrist skilled in performing these neuro-musculoskeletal exams which hampered our ability to determine inter-rater reliability and may limit generalizability (37,38). The reproducibility of these techniques and findings warrant confirmation, given our small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, study participants with pain had symptoms suggesting endometriosis which limited the number with pain without an endometriosis history. We did not assess sensitization in locations remote from the pelvis nor did we identify a second physiatrist skilled in performing these neuro-musculoskeletal exams which hampered our ability to determine inter-rater reliability and may limit generalizability (37,38). The reproducibility of these techniques and findings warrant confirmation, given our small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…40 It has been suggested that differences in muscular activity between the left and right limbs and morphological differences in the left and right hemibody may contribute to this laterality. 41 Treating MPS and MTrPs using a combined therapeutic approach is not novel. Hou and his team 7 claimed that IFT was superior to TENS when added to combination therapy for immediate improvements in cervical myofascial pain and trigger-point sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Barbero et al 150 reported ‘moderate to high’ intra-rater reliability of an experienced physiotherapist for determining the location of MTrPs within the upper trapezius muscle. However, in a recent systematic review on the reliability of physical examination for the diagnosis of myofascial TrPs, Lucas et al 144 concluded, ‘There is no accepted reference standard for the diagnosis of trigger points, and data on the reliability of physical examination for trigger points is conflicting’.…”
Section: Poor Inter-examiner Reliability For Trp Locationmentioning
confidence: 99%